2019
DOI: 10.1007/s12549-019-00389-0
|View full text |Cite
|
Sign up to set email alerts
|

Deperetomys (Rodentia, Muridae) from the Oligocene of Serbia and Bosnia and Herzegovina

Abstract: Two new late Oligocene species of Deperetomys: D. calefactus and D. saltensis, are described and the affinities between the various species are discussed. The new records extend the stratigraphic range of Deperetomys into the Oligocene, making it the first European Miocene murid that can be traced across the "Cricetid vacuum". A single M1 of a large early Oligocene murid that may represent the oldest record of Deperetomys is described. The classification problems that arise as a result of the fast increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In the chronology illustrated by Marković et al (2020), the earliest known Deperetomys appeared during the Oligocene, ca. 34–33 Ma (MP21–22).…”
Section: Systematic Paleontologymentioning
confidence: 98%
See 3 more Smart Citations
“…In the chronology illustrated by Marković et al (2020), the earliest known Deperetomys appeared during the Oligocene, ca. 34–33 Ma (MP21–22).…”
Section: Systematic Paleontologymentioning
confidence: 98%
“…They emended the generic diagnosis of Mein and Freudenthal (1971) and de Bruijn et al (1993). Because we lack upper molars of the Warm Springs cricetid, we refer only to the section of the diagnosis applying to the lower dentition, as follows (Marković et al, 2020, p. 833): “The m3 and m2 are about equally long. The m1 is rounded anteriorly.…”
Section: Systematic Paleontologymentioning
confidence: 99%
See 2 more Smart Citations
“…1) was compared with those from western Europe, Greece and Anatolia a geological age could be established and biogeographical provinces can be defined. The latest research of the Tertiary basins of the Central Balkans revealed the large similarity of forms belonging in the associations from Paragovo (Fruška Gora, Serbia) and Ugljevik -"Bogutovo Selo" (Bosnia and Herzegovina) (Marković et al 2019). Both are of Late Oligocene age.…”
Section: Some Scientific Resultsmentioning
confidence: 99%